Czynniki organizacyjne pracy zawodowej w ocenie nauczycielek edukacji wczesnoszkolnej - Maciąg, Jolanta (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
In all the deliberations concerning the conditioning of the teacher’s life, it is essential to pay attention to the organisational factors. Among those we can distninguish the external conditions of the teacher’s work in the context of which their activity takes place. Every single conditioning aspect can be the subject of a separate qualitative analysis. Therefore, in this author’s further considerations only certain organisational factors of career shall be presented – those that have been deemed essential and having influence on the degree of mutual interpersonal relations in teams in which the teachers of early education operate. This author arrived at the conclusion that it would be of value to analyse the very issue of interpersonal relations in the teachers’ environment. For the school’s activity is the more effective the more its teachers are able to cooperate smoothly, the better they understand one another and are able – with concentrated joint effort – to refine and improve the style of their respective individual work.